Coatings on glass - Pulker, H. K. (Hans K.), 1933-; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1999)
This is the second, revised edition of a book that has already proved invaluable to a wide range of readers. Written by a scientist for scientists and technical people, it goes beyond the subject matter indicated by the title, filling the gap which previously existed in the available technical literature. It includes a wealth of information for physicists, chemists and engineers who need to know more about thin films for research purposes, or who want to use this special form of solid material to achieve a variety of application-oriented goals.
Preface. 1. Introduction and history. 2. Composition, structure and properties of inorganic and organic glasses. 3. Nature of a surface. 4. Cleaning of substrate surfaces. 5. Glass and thin films. 6. Film formation methods. 7. Film thickness. 8. Properties of thin films. 9. Application of coatings on glass. Subject index.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Glass coatings; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Glass coatings; Electronic books